Manipulation of Dipolar Polarization at Steady States for a Quasi‐2D Organic–Inorganic Hybrid Perovskite with a Nanorod Network. Issue 3 (14th November 2019) - Yang, Hanjun; Wang, Kai; Deng, Liangliang; Yu, Haomiao; Li, Jinpeng; Hu, Bin
Abstract : Layered quasi‐2D organic–inorganic hybrid perovskites (OIHPs) prevent oxygen and moisture permeation, for long‐lifetime photovoltaic performance. Unfortunately, the electrical and photoinduced surface and dipolar polarizations caused due to the presence of the organic cation spacer in the structure remain unclear. Herein, a high‐performance planar quasi‐2D OIHP solar cell comprising (PEA)2 (MA)3 Pb4 I13 ( n  =   4) is designed. It displays a large area coverage and an interconnected nanorod network, which contributes to efficient light absorption and charge carrier transport. The surface and dipolar polarizations exhibit remarkable light intensity and electric field–dependent characteristics at short‐circuit‐current ( J sc ) and steady‐state (i.e., V oc ) conditions. More importantly, V oc exhibits a nonlinear behavior at steady states. Such a unique feature is in accordance with the dipolar polarization measured at the same condition. The phenomenon can be explained by the significant dipole–dipole interaction at lower electric field strengths. At higher field strengths, the screen of the dipoles due to charge accumulation at the surface of the organic cation spacer leads to slower increment of V oc . Thus, carefully designing the quasi‐2D perovskite nanostructure, together with the dielectric property of the organic cation spacer, may play an exceptionally important role for future high‐performance quasi‐2D perovskite solar cells. Abstract : Herein, the dipolar polarization in a quasi‐2D organic–inorganic hybrid‐perovskite nanorod network–based solar cell using impedance spectroscopy is studied. Electric field and photoinduced dipole–dipole interaction plays an important role for the solar cell working at steady states.